Gamma knife treatment for refractory cluster headache: prospective open trial. Issue 2 (14th January 2005) - Donnet, A; Valade, D; Régis, J
Abstract : Background: Since the initial report of Ford et al in 1998 no further study has evaluated radiosurgery of the trigeminal nerve in chronic cluster headache (CCH). Methods: We carried out a prospective open trial of neurosurgery and enrolled 10 patients (nine men, one woman; mean age 49.8 years, range 32–77) presenting with severe and drug resistant CCH (mean duration 9 years, range 2–33). The cisternal segment of the nerve was targeted with a single 4 mm collimator (80–85 Gy max). Results: The mean follow up was 13.2 months. No improvement was observed in two patients and three patients had no further attacks. Three patients showed dramatic improvement with a few attacks per month or very few attacks over the last six months. Two patients were pain free for only one and two weeks and their headaches recurred with the same severity as before. Three patients developed paraesthesia with no hypoaesthesia, one developed hypoaesthesia, and one developed deafferentation pain. Conclusions: The rate and severity of trigeminal nerve injury appeared to be significantly higher than in trigeminal neuralgia, and this study does not support the positive results of the study of Ford et al . We consider the morbidity to be significant for the low rate of pain cessation, making this procedure less attractive even for the more severely affected subgroup of patients.